The role of gibberellic acid and zinc sulfate on biochemical performance relate to drought tolerance of white bean under water stress - Abbasi, Arefeh; Maleki, Abbas; Babaei, Farzad; Safari, Hoshmand; Rangin, Alireza (Cellular and Molecular Biology, 2019)
In this study the effects of zinc sulfate and gibberellin on agro physiological of white bean under water deficiency were studied. Therefore, an experiment was conducted in a split-split plot design based on a randomized complete block with three replications in two places. The experimental factors included three irrigation levels, spraying of zinc sulfate in four levels and two levels of non-spraying and spraying of gibberellin. Analysis of measured data indicated that the water stress had a significant effect on all traits, except proline amount and 100 seeds weight. Spraying of zinc sulfate showed a significant effect on all traits except carotenoid value. Application of gibberellin had a significant effect on all traits except ion leakage, carotenoids, number of seeds per pod and grain yield. The interaction effect of stressí—zincsulfateí—gibberellin was significant on all traits except number of seeds per pod. In addition, comparison of means at 5% level, showed that application of 1.5 ml L-1of zinc sulfate plus gibberellin improved bean biochemical properties. Under optimum water level, using of 4.5 ml L-1of zinc sulfate and under severe water stress conditions, using of 4.5 ml L-1 of zinc sulfate plus gibberellin are recommended for obtaining the maximum crop performance.